Pollen species resources for Carpenter bees (Xylocopa spp.) in Central Sulawesi, Indonesia - SAMSURIZAL M. SULEMAN; MANAP TRIANTO; DIRHAM DIRHAM; LESTARI M. P. ALIBASYAH; HAYYATUN MAWADDAH (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Suleman SM, Trianto M, Dirham, Alibasyah LMP, Mawaddah H. 2025. Pollen species resources for Carpenter bees (Xylocopa spp.) in Central Sulawesi, Indonesia. Biodiversitas 26: 1503-1510. Pollen represents the microgametophyte generation in seed plants and plays a crucial role in their life cycle. Carpenter bees (Xylocopa spp.), known for their preference for forage plants with specific aroma and visual characteristics, play a significant role in the pollination process This study aimed to identify the plants producing pollen for carpenter bees in three districts of Central Sulawesi, Indonesia. The sampling of carpenter bees was carried out using the roaming method. The pollen samples from each bee leg were prepared using the acetolysis method to clear the pollen walls. Quantitative analysis was performed by counting 200-300 pollen grains in a single slide. Xylocopa confusa collects pollen from a diverse range of plant families, including Asteraceae, Arecaceae, Fabaceae, Poaceae, and others, while X. latipes relies on a more limited selection. Cocos nucifera serves as the predominant pollen source for both bee species. Additionally, X. confusa utilizes several Important Minor (IM) pollen sources, such as Desmodium adscendens, Euphorbia hirta, and Tetracera scandens, while Minor (M) pollen sources include Ageratum conyzoides, Sphagneticola trilobata, and others. Morphologically, most pollen grains are circular in polar view, with variations in equatorial shape, including prolate, subprolate, and semicircular forms. The highest pollen percentage is recorded for C. nucifera in both bee species.